Multiple intensity reference interferometry for the correction of sub-fringe displacement non-linearities - associated data - Bridges, Angus; Yacoot, Andrew; Kissinger, Thomas; Tatam, Ralph P. (Cranfield University, 2021)
Data associated with the publication "Multiple intensity reference interferometry for the correction of sub-fringe displacement non-linearities".
Keywords: Interferometry'; 'Non-linearity'; 'Dimensional Metrology'; 'Optical Physics not elsewhere classified'; 'Nanometrology'